Dynamic Gesture Recognition Based on Fusing Frame Images - Tingfang Zhang; Zhiquan Feng (2013 Fourth International Conference on Intelligent Systems Design and Engineering Applications, 2013)
With the rapid development of human-computer interaction technology, gesture recognition becomes one of the key technologies of human-computer interaction. In this paper, we propose a new method of dynamic hand gestures recognition. The method adopts the hierarchical identification model for dynamic hand gestures recognition. First, we combine frame fusion with density distribution features for rough gesture recognition, second, we use the Hausdorff distance or fingertip detection for accurate gesture recognition. The main innovation of this method lies in that we change the way of dynamic gestures recognition into the recognition of static image, improves the efficiency of gesture recognition effectively. Experimental results showed that our recognition rate is above 90%.